Tas Rajut Sebagai Sarana Bisnis dan Kreativitas Mahasiswa - Bahtiar, Erfan; Kurniawan, Deny; Wulandari, Sri Wahyuni; Widiarti, Wiwit (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2014)
Knitting bag is one of a kind handcrafted handbag that has a high exclusivity value in terms of price, shapes and colors. Crafts knitting bag employs students and worked with housewives and children of women who dropped out or just graduated of elementary school, Junior high school who didnt get a decent job because of there is no certificate. Methods of implementation include the preparation of materials, making the initial node, a process of production and marketing. For the bag and the resulting knit has its own uniqueness which makes is the same person. The determination of the sale price of the knitting bag hanging from the selection of materials and the difficulties level of making.Keywords : Knitting bag, ekslusivity,methods of implementation, and uniqueness.